2015
DOI: 10.1186/s40104-015-0046-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different forms of yeast Saccharomyces cerevisiae on growth performance, intestinal development, and systemic immunity in early-weaned piglets

Abstract: The present study was conducted to determine effects of different forms of yeast (Saccharomyces cerevisiae, strain Y200007) on the growth performance, intestinal development, and systemic immunity in early-weaned piglets. A total of 96 piglets (14-d old, initial average body weight of 4.5 kg) were assigned to 4 dietary treatments: (1) basal diet without yeast (Control); (2) basal diet supplemented with 3.00 g/kg live yeast (LY); (3) basal diet supplemented with 2.66 g/kg heat-killed whole yeast (HKY); and (4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
61
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 40 publications
10
61
1
2
Order By: Relevance
“…The benefits of intestinal health and immunomodulatory effects of yeast cells are important and represent the most likely benefits of supplementing pig diets with yeast (Liu et al ). Live yeast, finely ground live yeast and yeast fermentation products may lead to increased villus heights and villus‐to‐crypt ratios (Bontempo et al ; Shen et al ; Jiang et al ). Furthermore, significant longer villi and deeper crypts were found in the ileum of piglets receiving diets supplemented with S. cerevisiae spp.…”
Section: Probiotic Yeast For Pigsmentioning
confidence: 99%
See 2 more Smart Citations
“…The benefits of intestinal health and immunomodulatory effects of yeast cells are important and represent the most likely benefits of supplementing pig diets with yeast (Liu et al ). Live yeast, finely ground live yeast and yeast fermentation products may lead to increased villus heights and villus‐to‐crypt ratios (Bontempo et al ; Shen et al ; Jiang et al ). Furthermore, significant longer villi and deeper crypts were found in the ileum of piglets receiving diets supplemented with S. cerevisiae spp.…”
Section: Probiotic Yeast For Pigsmentioning
confidence: 99%
“…In addition, the requirement for yeast extracts containing nucleotides may be increased under certain conditions, such as high stress, during disease, or rapid growth (Waititu et al ). The weaning itself causes villus atrophy and reduces replacement of enterocytes both of which inhibit the absorption of nutrients, a part of easing the transition around weaning of pigs involves preparing the intestine to change in diet form that caused a possible deficiency of nucleotides and in that case, yeast cells may be potentially beneficial (Jiang et al ).…”
Section: Probiotic Yeast For Pigsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrated the ability of nucleotides extracted from yeast to re‐governing intestinal microbiota and improving growth performance and health status in piglets, through the increase in IGF‐1 and GH (Jiang et al., ). Alternatively, IGF binding protein‐2 (IGFBP‐2) is a secreted protein that binds and reduces IGF actions in controlling growth, development, reproduction and aging (Zhou et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The dietary supplementation of live yeast, yeast cultures, or yeast cell‐wall products has positively influenced the performance and health of weaned piglets by mitigating negative effects associated with stress and disease . Yeast or yeast‐based product supplementation has also been demonstrated to boost feed intake, augment mucosal immunity, promote intestinal development, modulate gut microbiota, and reduce post‐weaning diarrhea . The components of yeast cell walls, which are made up of β ‐ d ‐glucans and α ‐ d ‐mannans, are considered to be responsible for their positive effects .…”
Section: Introductionmentioning
confidence: 99%